Food security in the economic security of the national economy - V. I. Menshchikova; A. M. Greshonkov; L. M. Abramova (Путеводитель предпринимателя)
The article proves that achieving food security in the modern geopolitical conditions associated with finding a balance between dependence on foreign contractors supplyingfood (import) and domestic food production (import substitution), especially in the framework of the Customs Union and the integration processes between the BRICS countries. Justified by the idea that the development of the conceptual foundations offood security doctrine should start from the concept of«consumer basket, the necessary economic entity for a comfortable stay,» and identified the key areas related to the implementation of the doctrine.